2002
DOI: 10.1046/j.1365-2133.2002.04803.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor and substance P are useful plasma markers of disease activity in atopic dermatitis

Abstract: These data represent the first reported evidence of increased plasma levels of NGF and SP in an allergic human skin disease. They suggest that these neurogenic factors systemically modulate the allergic response in AD, probably through interactions with cells of the immune-inflammatory component. In addition, NGF and SP may be useful markers of disease activity in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
179
3
16

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(214 citation statements)
references
References 70 publications
14
179
3
16
Order By: Relevance
“…However, several experimental studies have suggested an indirect pruritogenic effect of above cytokines via other mediators (55,58). Furthermore, hBDs and LL-37 elicited the expression or release of the most potent pruritogens, including substance P, PGE 2 , LTC 4 , and NGF (42,(59)(60)(61). These observations provide novel evidence that hBDs and LL-37 may participate in inflammatory and/or allergic reactions via the activation of mast cells.…”
Section: Discussionmentioning
confidence: 73%
“…However, several experimental studies have suggested an indirect pruritogenic effect of above cytokines via other mediators (55,58). Furthermore, hBDs and LL-37 elicited the expression or release of the most potent pruritogens, including substance P, PGE 2 , LTC 4 , and NGF (42,(59)(60)(61). These observations provide novel evidence that hBDs and LL-37 may participate in inflammatory and/or allergic reactions via the activation of mast cells.…”
Section: Discussionmentioning
confidence: 73%
“…NGF protein levels are increased in psoriatic skin compared to non-lesional and normal skin (14), and psoriatic keratinocytes express higher amounts of NGF than normal keratinocytes (15). Patients with atopic dermatitis also showed significant gains in NGF plasma levels compared to controls, and a strong correlation was noted between plasma NGF and severity of symptoms (16). These findings suggest that NGF may play an important role in the pathogenesis of atopic dermatitis, possibly regulating the development of atopic dermatitis lesions.…”
Section: Introductionmentioning
confidence: 69%
“…Recent studies have documented increased levels of nerve growth factor and substance P in plasma of AD patients which correlated positively with disease activity 22 . Brainderived growth factor, detected recently in sera and plasma of patients with AD, enhances the survival of eosinophils while increasing their chemotactic response in vitro 23 .…”
Section: ) Neuroimmunological Factorsmentioning
confidence: 99%